(untitled) (Journal of Engineering, 2024)
In Iraq, as well as many other developing countries the performance graded (PG) based System is not yet implemented to evaluate the currently used asphalt cernents for paving works. It appears that not only the unavailability of test equipments is resulting in this delay but also the lack of clear understanding of what steps could be taken to incorporate this system. This research is an attempt to highlight the important aspects of a (PG) system that can be readily implemented without the need for expensive equipments. It includes the development of a Performance based System employing the conventional test methods and available nomographs from literature. It also, shows how climatic data, traffic data, and asphalt binder properties can be combined to propose a possible major improvement for the specifications of asphalts in Iraq. To achieve the objective of this research, an extensive air temperature data for a period of 18 years was reviewed for five cities (Mosul. Kirkuk. Rutba, Baghdad, and Basrah) to establish the required PG asphalt binder for each city. Also, the currently used asphalt cements with penetration grades (40-50) and (60-70) were tested by both of conventional test methods and Superpave methods to determine the equivalent performance grade for each type of the penetration graded asphalt and to evaluate the capability for these two types of asphalt cement to satisfy the required performance of pavement for each city, The results indicate that both the new proposed method and Superpave method give the same final performance grade. The asphalt with penetration grade 40-50 is equivalent to PG70-16 while that with penetration grade 60-70 is equivalent to PG64-16